2021
DOI: 10.3390/nu13072445
|View full text |Cite
|
Sign up to set email alerts
|

Fast Anxiolytic-Like Effect Observed in the Rat Conditioned Defensive Burying Test, after a Single Oral Dose of Natural Protein Extract Products

Abstract: Anxiety appears among the most frequent psychiatric disorders. During recent years, a growing incidence of anxiety disorders can be attributed, at least in part, to the modification of our eating habits. To treat anxiety disorders, clinicians use benzodiazepines, which unfortunately display many side effects. Herein, the anxiolytic-like properties of two natural products (αS1–casein hydrolysate and Gabolysat®) were investigated in rats and compared to the efficacy of benzodiazepine (diazepam). Thus, the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The total study population had quite similar characteristics to those of the Stress 2 study: mean age 43 years (18-68 years), 66.1% female, family-related stressors in 40.7%, occupational stressors in 29.6% and health-related stressors in 8.5% of patients. The mean Ham-A score at inclusion was 25.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) Although the supplementation does not reduce anxiety to the same extent as anxiolytics, its efficacy is not negligible compared to the results of the Nguyen et al study [35], particularly with regard to its tolerability (see below). The PGI, which assesses patients' feelings (not collected in the Nguyen et al study), supports these encouraging results for the tested dietary supplement.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The total study population had quite similar characteristics to those of the Stress 2 study: mean age 43 years (18-68 years), 66.1% female, family-related stressors in 40.7%, occupational stressors in 29.6% and health-related stressors in 8.5% of patients. The mean Ham-A score at inclusion was 25.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) Although the supplementation does not reduce anxiety to the same extent as anxiolytics, its efficacy is not negligible compared to the results of the Nguyen et al study [35], particularly with regard to its tolerability (see below). The PGI, which assesses patients' feelings (not collected in the Nguyen et al study), supports these encouraging results for the tested dietary supplement.…”
Section: Discussionmentioning
confidence: 91%
“…In rats, Gabolysat ® showed an anxiolytic activity comparable to that of diazepam as early as 30 min after its administration as well as 60 min after. Therefore, Gabolysat ® has the advantage of acting rapidly and durably on anxiety [36]. The efficacy of the supplement could be explained by the combination of active ingredients that act on the GABAergic system.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the use of protein lysates from various food sources has seen increasing interest because of their biological activities. Bioactive peptides from a fish protein hydrolysate, named Gabolysat ® , exhibited anxiolytic effects in a conditional burying test [ 22 ] and are able to modulate stress responses by acting on the pituitary–adrenal axis, on sympathoadrenal activity and on gamma-aminobutyric acid content [ 23 ]. In addition, the combination of Gabolysat ® with magnesium and vitamin B6 has also been proven to be efficient with respect to adjusting anxiety disorders [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, Bernet et al demonstrated the diazepam-like effect of fish protein hydrolysate supplementation (1.2 mg·kg −1 ) on stress responsiveness [ 10 ], whereas Messaoudi et al demonstrated the potential anxiolytic- and antidepressant-like properties of a protein autolysate from the blue ling fish, in the absence of any changes in cerebral activation or dependence [ 11 ]. More recently, Freret et al showed that both the natural products, αS1–casein hydrolysate and fish hydrolysate (oral dose of 15 mg·kg −1 ), were as efficient as diazepam in reducing anxiety levels in rats, along with fast-acting anxiolytic activity of the fish hydrolysate [ 12 ]. Of note, the results of a study by Messaoudi et al suggested the antistress activity of αS1-casein hydrolysate in human subjects based on changes in blood pressure and cortisol levels, confirming the interest in natural hydrolysates for stress management [ 13 ].…”
Section: Introductionmentioning
confidence: 99%